Community power in harnessing Kansas wind: An academic/practice partnership to assess the implications of community engagement in the development of sustainable wind energy projects - Ballard-Reisch, Deborah; Koeber, Charles; Granville, Melissa; Fletcher, Jeff (Kansas State University, 2011)
Kansas ranks 2nd in wind-producing potential in the United States (Lu et al., 2009), yet wind energy generation currently contributes only minimally to the State’s electricity supply (“Kansas”, 2008). As of August 2010, Kansas had only 8 operational commercial wind energy projects; with State goals to generate at least 20% of electricity from renewable energy sources by 2020, wind energy project development will increase (“Annual”, 2010). This presentation reports on a community-based participatory research project to assess perceptions of community involvement in commercial wind project development in 3 Kansas counties (Wabaunsee, Kiowa, Butler). Through key informant interviews, focus groups, and document analysis, graduate students in a qualitative research methods course engaged in data-driven inductive and theory- driven deductive thematic analyses (Boyatzis, 1998) in order to study the development of wind energy projects, the importance of community involvement and collaboration, and the implications of both process and response for project sustainability. This unique academic/practice partnership built skills in student participants and contributed to an understanding of the factors that impact the sustainability of wind energy projects. Additionally, implications of project findings for state policy, stakeholder engagement, and wind developer practice are discussed.
Keywords: Wind power; Kansas; Wind energy projects; Community involvement